Dynamic HTML 4.X ([ S.l.] : Keystone Learning Systems, 1999)
Level 1- Introduction, What can I do with Microsoft Dynamic HTML?, Dynamic TexRange, TextRange object navigation ; Level 2 - TextRange object content selection, Advanced TextRange object programming, Dynamic styles, Programming styles ; Level 3 - Dynamic CSS positing, Text animation, Dynamic content
Professional trainer & Internet instructor, Robert Machale
System requirements: Windows 95 or NT 4.0 or later, at least 8 MB RAM, 1MB hard disk space, audio card
Keywords: HTML (Document markup language)